Fractional Banking System with the Unknown Risk (see verses) - Jilani Ben Touhami Meftah (International Journal of Nusantara Islam, 2013)
The fractional banking system to day is the basis banking transactions, it is the engine of economic processes in the global banking and the seed that grew out of the economies around the globe and the main factor attributed to the successes of the global economy and its failures. Perhaps the most important reasons for this neglect is the adoption of thought Islamic Economics contemporary, and the seriousness of this matter is fractional banking is some of the descriptions on the origins of the law and rules.